2020
DOI: 10.3390/w12113139
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Multistage Constructed Wetland for Municipal Wastewater Treatment and Reuse for Agriculture in Senegal

Abstract: This paper reports on the performance of using a multistage constructed wetland (CW) to treat municipal raw wastewater and an analysis of its suitability for agricultural irrigation. The pilot plant consists of two stages of vertical flow CWs plus one stage of a horizontal CW built in 2018 with different local materials at the Gaston Berger University Campus, Saint Louis (Senegal). Each CW stage is composed of several filters with different type of media (silex, granite, or river gravel), filtering media depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
0
16
0
2
Order By: Relevance
“…This was due to the combination of different types of CWs, allowing various removal mechanisms to occur at various intensities (aerobic and anaerobic degradation, adsorption, filtration, volatilisation, photodegradation, etc.). The elimination of nitrogen can also be enhanced, since both nitrification and denitrification can take place [48,50,52].…”
Section: Discussion On Cws Performances Under Different Design and Op...mentioning
confidence: 99%
See 4 more Smart Citations
“…This was due to the combination of different types of CWs, allowing various removal mechanisms to occur at various intensities (aerobic and anaerobic degradation, adsorption, filtration, volatilisation, photodegradation, etc.). The elimination of nitrogen can also be enhanced, since both nitrification and denitrification can take place [48,50,52].…”
Section: Discussion On Cws Performances Under Different Design and Op...mentioning
confidence: 99%
“…The intensity of these different removal mechanisms varies according to the type of the CWs, water chemistry, retention time, seasonal variation, substrate, and vegetation [78,79]. Although several studies showed substantial elimination of microbial contamination reaching over 99% [36,39,50,52,80], other studies showed lower removal rates [51]. The removal of microbial contamination in CWs is still challenging, and the implementation of polishing step, such as disinfection using chemical agents or UV lights, is recommended if the treated wastewater is to be reused in agriculture [22,43].…”
Section: Discussion On Cws Performances Under Different Design and Op...mentioning
confidence: 99%
See 3 more Smart Citations